Are Poland and Canada: Becoming Close Partners? - Kamiński, Tomasz (The Copernicus Journal of Political Studies, 2018)
The author presents relations between Canada and Poland in 21st century. He explains the reasons for the lack of close connections between the two countries. Then, he recognizes few historical links, focusing on Polish migration to Canada. Afterwards, he describes official diplomatic relations by presenting meetings of politicians from both countries in 20th century. The foundation of relations between countries in modern world is economics, which is presented in next part. The author presents facts about trade and investment. In next part, he describes the Polish community in Canada, focusing on the Canadian Polish Congress and other organizations that play an important role in life of Polish minority. Finally, the two most important events of last decade of bilateral relations are presented: death of a Polish immigrant that was tasered in Vancouver and recent takeover of Quadra FNX, a Canadian mining company, by the Polish copper corporation KGHM. The author describes the incident with Robert Dziekanski, presenting the reaction to it by Canadians and Poles, as well as the results of the investigation. He also gives facts about KGHM’s purchase of Quadra FNX and explains what this transaction means to the Polish company. The author concludes by deliberating about perspectives of relations between Canada and Poland. Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14761